Scutellarin Prevents Angiogenesis in Diabetic Retinopathy by Downregulating VEGF/ERK/FAK/Src Pathway Signaling - Lingli Long; Yubin Li; Shuang Yu; Xiang Li; Yue Hu; Tengfei Long; Liqin Wang; Wenwen Li; Xiaoxin Ye; Zunfu Ke; Haipeng Xiao (Journal of Diabetes Research)
Background. Diabetic retinopathy (DR) is a serious microvascular complication of diabetes. This study demonstrates the antiangiogenic effects of scutellarin (SCU) on high glucose- and hypoxia-stimulated human retinal endothelial cells (HRECs) and on a diabetic rat model by oral administration. The antiangiogenic mechanisms of SCU in vitro and in vivo were investigated. Method. HRECs were cultured in high glucose- (30 mM D-glucose) and hypoxia (cobalt chloride-treated)-stimulated diabetic condition to evaluate the antiangiogenic effects of SCU by CCK-8 test, cell migration experiment (wound healing and transwell), and tube formation experiment. A streptozotocin-induced type II diabetic rat model was established to measure the effects of oral administration of SCU on protecting retinal microvascular dysfunction by Doppler waveforms and HE staining. We further used western blot, luciferase reporter assay, and immunofluorescence staining to study the antiangiogenic mechanism of SCU. The protein levels of phospho-ERK, phospho-FAK, phospho-Src, VEGF, and PEDF were examined in HRECs and retina of diabetic rats. Result. Our results indicated that SCU attenuated diabetes-induced HREC proliferation, migration, and tube formation and decreased neovascularization and resistive index in the retina of diabetic rats by oral administration. SCU suppressed the crosstalk of phospho-ERK, phospho-FAK, phospho-Src, and VEGF in vivo and in vitro. Conclusions. These results suggested that SCU can be an oral drug to alleviate microvascular dysfunction of DR and exerts its antiangiogenic effects by inhibiting the expression of the crosstalk of VEGF, p-ERK, p-FAK, and p-Src.